Alpha 1 Antitrypsin therapy in patients with Alpha 1 Antitrypsin deficiency: perspectives from a registry study and practical considerations for self-administration during the COVID-19 pandemic - Herth, Felix; Sandhaus, Robert A.; Turner, Alice M.; Sucena, Maria; Welte, Tobias; Greulich, Timm (The International journal of chronic obstructive pulmonary disease, 2021)
The challenges of providing alpha 1 antitrypsin therapy during the COVID-19 pandemic and the potential considerations for its implementation thereafter